The Effect of Traditional Food on Tourist Intention to Visit Bogor City - Setiawan, Daniel Gernando (SABA: Journal of Tourism Research, 2023)
This research aims to enhance our understanding of the impact of culinary aspects on the tourism sector, particularly with a focus on Bogor City. Additionally, it aims to provide related information to stakeholders involved in enhancing culinary promotion strategies within Bogor City and, by extension, contribute substantively to advancing tourism research and development in Indonesia. The study's dataset consisted of 100 respondents with no experience visiting Bogor City. The independent variable in this study is the Tourist Perception of Traditional Food, whereas the dependent variable is the Tourist Intention to Visit Bogor City. The primary tool used for data collection is a questionnaire. Meanwhile, the analytical approach includes descriptive statistical techniques and simple linear regression models. The findings of this study explain the extent of the influence of tourists' perceptions of traditional food in Bogor on their tendency to visit the city. Empirical results show a statistically significant influence of 60%, thus forming a positive relationship between tourists' perceptions of traditional Bogor food and their tendency to visit Bogor City. Therefore, tourists' perceptions of Bogor's traditional food have a reasonable correlation with their intention to explore Bogor City as a tourist destination.